2020
DOI: 10.1007/s00779-020-01364-9
|View full text |Cite
|
Sign up to set email alerts
|

Supporting intergenerational memento storytelling for older adults through a tangible display: a case study

Abstract: Mementoes act as emotional companions that anchor stories. Older adults typically have a rich knowledge of family mementoes. However, storytelling and preservation of mementoes are still problematic for them: their mementoes are still mostly in physical format, which is difficult to share and preserve. Additionally, digital applications and websites for sharing mementoes usually are inaccessible for them. As a result, they spend much time collecting mementoes, but spend less time on telling and recording the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
5
0
4
Order By: Relevance
“…Li et al [4] introduce the design and implementation of a tangible device, Slots-Memento, that supports intergenerational memento storytelling for older adults. The authors argue that memento sharing is a cooperation process that should involve both the storytellers and listeners.…”
Section: Accepted Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [4] introduce the design and implementation of a tangible device, Slots-Memento, that supports intergenerational memento storytelling for older adults. The authors argue that memento sharing is a cooperation process that should involve both the storytellers and listeners.…”
Section: Accepted Articlesmentioning
confidence: 99%
“…This special issue revealed that there are yet some challenges that need to be addressed for pervasive displays and proposed solutions. This includes technical challenges, such as content scheduling [13], as well as human-centered design challenges, such as attracting attention [2], social acceptability [10], workload [8], and designing for different user groups [4,6]. Authors of articles in this special issue have shown that these areas require further research, and have also highlighted multiple opportunities which we divide in terms of use cases and methodologies: Novel use cases: There is a myriad of use cases for which pervasive displays can be particularly promising.…”
Section: The Future Of Pervasive Displaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 unfolds the quantity proportions of trigger questions chosen by the young. For the mementos, the categorization followed our previous research [35], we classified them into three types, and from high to low they were a photo, object, and paper document. The photo was divided into family member, activity, friend, marriage, object, et cetera., depending on their themes.…”
Section: Design Case Two: Story2sharementioning
confidence: 99%
“…Επίσης, το άκουσμα της φωνής ενός προσώπου μπορεί να ενδυναμώσει στον ακροατή την οπτική και συναισθηματική αναδόμηση του χρόνου, του χώρου και των ευρύτερων στοιχείων μιας ανάμνησης (Oleksik & Brown, 2008). Η αξία των προαναφερθέντων ιδιοτήτων είχε ως αποτέλεσμα τη δημιουργία διαφόρων τεχνολογικών καινοτομιών που βασίζονται στον ήχο, όπως είναι η Memory Tree (Jayaratne, 2016), η FM Radio (Petrelli et al, 2010), η EatWell (Grimes et al, 2008), η Slots-Memento (Li et al, 2020), η Kurios (Tolentino & Mosher, 2020) κ.ά. Ωστόσο, σε συγκεκριμένες περιπτώσεις, οι ηχογραφήσεις χαρακτηρίζονται από ορισμένα μειονεκτήματα.…”
Section: ερευνητικά ερωτήματαunclassified